2007
DOI: 10.1108/17549450200700017
|View full text |Cite
|
Sign up to set email alerts
|

Talking Mats: the effectiveness of a low technology communication framework to help people with dementia express their views

Abstract: The aims of this project were to establish whether Talking Mats, a low tech communication framework, helps people with dementia to communicate and to examine how effective the Talking Mats framework is for people at different stages of dementia. Thirty‐one people at three stages of dementia were interviewed about their well‐being under three interview conditions ‐ an unstructured (ordinary) conversation, a structured conversation and using the Talking Mats framework.The results indicated that conversations usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 7 publications
0
51
0
Order By: Relevance
“…Previous research had identified that photographs and pictures enhance communication with people with intellectual disability (Jackson & Jackson 1999), particularly when offering bereavement counselling and support (Hollins & Sireling 1991; Read 1999; Tuffrey‐Wijne & Bernal 2003 ). In addition, there exists some precedents for image‐based techniques; what is essentially a modified version of the Repertory Grid, known as ‘Talking Mats’, has been used successfully with people with severe intellectual disability (Bell & Cameron 2003) and dementia (Murphy et al. 2007).…”
Section: Materials Methods and Proceduresmentioning
confidence: 99%
“…Previous research had identified that photographs and pictures enhance communication with people with intellectual disability (Jackson & Jackson 1999), particularly when offering bereavement counselling and support (Hollins & Sireling 1991; Read 1999; Tuffrey‐Wijne & Bernal 2003 ). In addition, there exists some precedents for image‐based techniques; what is essentially a modified version of the Repertory Grid, known as ‘Talking Mats’, has been used successfully with people with severe intellectual disability (Bell & Cameron 2003) and dementia (Murphy et al. 2007).…”
Section: Materials Methods and Proceduresmentioning
confidence: 99%
“…Talking Mats is now an established communication tool world-wide, both in clinical practice and in research (Cameron & Murphy,2001, 2002Gillespie, Place, & Murphy, 2010;Murphy, 2006;Murphy & Cameron, 2008;Murphy, Cameron, Markova, & Watson, 2004;Murphy, Gray, & Cox, 2007;Murphy, Gray, Cox, van Achterberg, & Wyke, 2010). It is also used internationally in countries as diverse as Scandinavia, China, Malta, Croatia, South Africa, and Australia and is recognized as a tool that enables people of all ages with communication difficulties to be actively involved in expressing their own views (Bell & Cameron, 2003;Brewster, 2004;Bunning & Steel, 2006;Clare & Cox, 2003;Di Marco & Iacono, 2007;Dougall & Fiske, 2008;Germain, 2004;Grieveo, McLaren, & Lindsay, 2006;Hooton & Westaway, 2008;Pawson, Raghavan, & Small, 2005;Raghavendra, Bornman, Granlund, & Björck-Åkesson, 2007;Taylor, 2007;Whitehurst, 2006;young & Chesson, 2007).…”
Section: The Talking Mats Frameworkmentioning
confidence: 97%
“…Previous studies (Murphy et al. 2004, 2007, 2010a) found that the Talking Mats framework could be used by many (although not all) people at early, middle and late stages of dementia and that it improved their ability to communicate compared with usual conversation.…”
Section: Talking Mats®mentioning
confidence: 99%
“…Previous studies (Murphy et al , 2007(Murphy et al , 2010a found that the Talking Mats framework could be used by many (although not all) people at early, middle and late stages of dementia and that it improved their ability to communicate compared with usual conversation. In particular, for people with early (and some with moderate) stage dementia, Talking Mats increased the period of time that their conversation stayed on track and the extent to which a communication partner understood their views.…”
Section: Talking Mats òmentioning
confidence: 99%